Oxidation of Free, Peptide and Protein Tryptophan Residues Mediated by Aaph-Derived Free Radicals: Role of Alkoxyl and Peroxyl Radicals - Lissi-Gervaso, E; Aspee-Lamas, A; Pino-Lopez, E (Royal Society of Chemistry, 2016)
The oxidation of tryptophan (Trp) residues, mediated by peroxyl radicals (ROO), follows a complex mechanism involving free radical intermediates, and short chain reactions. The reactivity of Trp towards ROO should be strongly affected by its inclusion in peptides and proteins. To examine the latter, we investigated (by fluorescence) the kinetic of the consumption of free, peptide- and protein-Trp residues towards AAPH (2,2′-azobis(2-amidinopropane)dihydrochloride)-derived free radicals. Interestingly, the initial consumption rates (Ri) were only slightly influenced by the inclusion of Trp in small peptides and proteins (human serum albumin and human superoxide dismutase). Depending on the Trp concentration, the Riversus Trp concentration ([Trp]) plots showed three regions. At low Trp concentrations (1-10 μM), a linear dependence was observed between Ri and [Trp]; at intermediate Trp concentrations (10-50 μM), the values of Ri were nearly constant; and at high Trp concentrations (50 μM to 1 mM), a slower increase of Ri than expected for chain reactions. Similar behavior was detected for all three systems (free Trp, and Trp in peptides and proteins). For the first time we are showing that alkoxyl radicals, formed from self-reaction of ROO, are responsible of the Trp oxidation at low concentrations, while at high Trp concentrations, a mixture of peroxyl and alkoxyl radicals are involved in the oxidation of Trp residues. This journal is © The Royal Society of Chemistry 2016.